Accuracy assessment of the traffic safety module on two-lane rural roads - Girdvainis, Romas; Bertulienė, Lina; Juknevičiūtė-Žilinskienė, Lina; Vorobjovas, Viktoras; Gintalas, Vilimas (International Conference “Environmental Engineering”, 2023)
EU countries use a design methodology based on the traffic safety module, proposed by the German scientist R. Lamm. This methodology makes it possible to identify potentially high-risk sections of the road that can become dangerous sections or “black spots” in the future, even at the design stage. This methodology has not yet been implemented in the provisions of the Lithuanian road design normative documents. During the analysis of the traffic safety module results obtained during the previous research carried out by the authors, the impression was created that some of them are wrong. Therefore, in this research, it was decided to also perform a natural experiment by passing the investigated road sections by car. The purpose of this research is to evaluate the accuracy of R. Lamm traffic safety module. The paper presents results of the experiment and their comparison with the predictions of theoretical research.
Keywords: curvature change rate; traffic safety module; turning angle; two-lane road